Understanding Religious Change in Africa and Europe: Crossing Latitudes: The Christianization of Jukun of Nigeria and Celtic Irish in Early Medieval Europe - Elawa, Nathan (Springer International Publishing, 2020)
Chapter 1. Crossing the Latitudes: Religious Change Among the Jukun and the Irish -- Chapter 2. General History of the Jukun with a Brief History of Early Ireland -- Chapter 3. Window into the Jukun Worldview: Understanding the Pillars of ‘Wa’ -- Chapter 4. Patrilineal and Patriarchy: Understanding Early Irish Kinship -- Chapter 5. Jukun understanding of Personhood -- Chapter 6. Early Irish understanding of personhood -- Chapter 7. Jukun Microcosm of the Ando (large homestead) Contrasted with Irish Muintir (large home) -- Chapter 8. Larger Macrocosm: the Fintswen and the Tuath -- Chapter 9. External influences on Jukun and Irish Society and Religion -- Chapter 10. Reappraisal of Western Missions in Africa and its Diaspora and Romanization in Early Medieval Europe Contrasted -- Chapter 11. Religious Change, Indigenous Cosmologies and Christianity -- Conclusion.